Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Certainly! Let's solve the system of equations step-by-step.
We have the following system of equations:
[tex]\[ \left\{ \begin{array}{c} y = -6x - 16 \\ y = x^2 - 7 \end{array} \right. \][/tex]
To solve this system, we need to find the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that satisfy both equations. Here is the step-by-step solution:
1. Set the equations equal to each other:
Since both equations are equal to [tex]\( y \)[/tex], we can set them equal to each other:
[tex]\[ -6x - 16 = x^2 - 7 \][/tex]
2. Rearrange the equation:
Bring all terms to one side of the equation to set it to zero:
[tex]\[ x^2 + 6x + 9 = 0 \][/tex]
3. Factor the quadratic equation:
Notice that [tex]\( x^2 + 6x + 9 \)[/tex] is a perfect square trinomial. We can factor it as follows:
[tex]\[ (x + 3)^2 = 0 \][/tex]
4. Solve for [tex]\( x \)[/tex]:
Set each factor equal to zero:
[tex]\[ x + 3 = 0 \][/tex]
Solve for [tex]\( x \)[/tex]:
[tex]\[ x = -3 \][/tex]
5. Solve for [tex]\( y \)[/tex]:
Use the value of [tex]\( x \)[/tex] in either of the original equations to find [tex]\( y \)[/tex]. Let's use the first equation [tex]\( y = -6x - 16 \)[/tex]:
[tex]\[ y = -6(-3) - 16 \][/tex]
Simplify:
[tex]\[ y = 18 - 16 \][/tex]
Thus:
[tex]\[ y = 2 \][/tex]
6. Write the solution:
We have found that [tex]\( x = -3 \)[/tex] and [tex]\( y = 2 \)[/tex]. Therefore, the solution to the system of equations is:
[tex]\[ (-3, 2) \][/tex]
So, the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that satisfy both equations are [tex]\( x = -3 \)[/tex] and [tex]\( y = 2 \)[/tex].
We have the following system of equations:
[tex]\[ \left\{ \begin{array}{c} y = -6x - 16 \\ y = x^2 - 7 \end{array} \right. \][/tex]
To solve this system, we need to find the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that satisfy both equations. Here is the step-by-step solution:
1. Set the equations equal to each other:
Since both equations are equal to [tex]\( y \)[/tex], we can set them equal to each other:
[tex]\[ -6x - 16 = x^2 - 7 \][/tex]
2. Rearrange the equation:
Bring all terms to one side of the equation to set it to zero:
[tex]\[ x^2 + 6x + 9 = 0 \][/tex]
3. Factor the quadratic equation:
Notice that [tex]\( x^2 + 6x + 9 \)[/tex] is a perfect square trinomial. We can factor it as follows:
[tex]\[ (x + 3)^2 = 0 \][/tex]
4. Solve for [tex]\( x \)[/tex]:
Set each factor equal to zero:
[tex]\[ x + 3 = 0 \][/tex]
Solve for [tex]\( x \)[/tex]:
[tex]\[ x = -3 \][/tex]
5. Solve for [tex]\( y \)[/tex]:
Use the value of [tex]\( x \)[/tex] in either of the original equations to find [tex]\( y \)[/tex]. Let's use the first equation [tex]\( y = -6x - 16 \)[/tex]:
[tex]\[ y = -6(-3) - 16 \][/tex]
Simplify:
[tex]\[ y = 18 - 16 \][/tex]
Thus:
[tex]\[ y = 2 \][/tex]
6. Write the solution:
We have found that [tex]\( x = -3 \)[/tex] and [tex]\( y = 2 \)[/tex]. Therefore, the solution to the system of equations is:
[tex]\[ (-3, 2) \][/tex]
So, the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that satisfy both equations are [tex]\( x = -3 \)[/tex] and [tex]\( y = 2 \)[/tex].
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.